Anatomical feature and early outcomes of endovascular aneurysm repair from King Chulalongkorn Memorial Hospital - Kritayakirana, Kritaya; Narueponjirakul, Natawat; Uthaipaisanwong, Apinan; Chanpen, Nantiskarn; Aimsupanimitr, Punthita (Chulalongkorn Medical Journal, 2021)
Background: Many studies have evaluated anatomy of infrarenal abdominal aortic aneurysm (AAA) and outcomes after endovascular abdominal aneurysm repair (EVAR) but mostly in non-Asian populations. The objective of this study was to evaluate anatomical features and early outcomes for EVAR in the Thai population in a single-center experience. Objective: Treatment of AAA with suitable anatomy has been trending towards EVAR. This study aimed to analyze anatomical features and early outcomes of EVAR in Thai population at King Chulalongkorn Memorial Hospital (KCMH). Methods: Retrospective review of 82 patients who underwent EVAR since January 2012 to December 2016. The medical records were analyzed for demographic data, anatomical features of AAA and outcomes in 30 days. Results: Presentations were asymptomatic 38 cases (46.0%), symptomatic 19 cases (23.0%), ruptured AAA 13 cases (16.0%), and mycotic aneurysm 12 cases (15.0%). Anatomical features of the neck and aortic aneurysms in all groups were similar. Overall mortality was found 7 cases (8.5%). The ruptured group had a significantly higher mortality rate 4 cases (30.0%). Conclusion: Anatomical features of AAA at KCMH were similar to other Asian populations. Early outcome of EVAR in asymptomatic, symptomatic, and mycotic aortic aneurysm was good. Thirty-day mortality was higher in ruptured AAA patients. Emergency and urgency conditions to treat AAA did not affect procedure-related complications. Iliac limb stent graft occlusion tends to occur in distal landing zone in the external iliac artery.